2021
DOI: 10.3390/ijerph18168456
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Dynamic Linkage between Tourism Development, Technological Innovation, Urbanization and Environmental Quality: Provincial Data Analysis of China

Abstract: This study investigates the linkage between tourism development, technological innovation, urbanization and environmental degradation across 30 provinces of China. Based on data from 2001 to 2018, the study used an advanced economic methodology for the long-run estimate, the Augmented Mean Group (AMG) estimator, which accounts for heterogeneity in slope parameters and dependencies across countries. The empirical results show that tourism development degrades environmental quality, while technological innovatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 64 publications
0
12
0
Order By: Relevance
“…Facing a post-COVID-19 era, tourism, which contributes over 10% to global economic growth [ 1 ], may play a significant role in economic recovery. However, over the past several years, the tourism industry has seen an increase in the consumption of natural resources and energy [ 2 ] as well as significant increases in carbon emissions and the disposal of other types of waste [ 3 ]. Because the tourism industry has an extremely complex input–output relationship and involves a large number of intermediate input sectors on its supply chain [ 4 ], some scholars have begun to use the input–output method to evaluate carbon emissions in the supply chain of tourism [ 5 , 6 ]; furthermore, scholars have found that global carbon emissions, including indirect emissions from the supply chain, are four times higher than the direct carbon emissions of tourism [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Facing a post-COVID-19 era, tourism, which contributes over 10% to global economic growth [ 1 ], may play a significant role in economic recovery. However, over the past several years, the tourism industry has seen an increase in the consumption of natural resources and energy [ 2 ] as well as significant increases in carbon emissions and the disposal of other types of waste [ 3 ]. Because the tourism industry has an extremely complex input–output relationship and involves a large number of intermediate input sectors on its supply chain [ 4 ], some scholars have begun to use the input–output method to evaluate carbon emissions in the supply chain of tourism [ 5 , 6 ]; furthermore, scholars have found that global carbon emissions, including indirect emissions from the supply chain, are four times higher than the direct carbon emissions of tourism [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The causative based test advocated a bidirectional connectedness from transportation, tourism development, economic growth, and energy consumption in the direction of CO 2 emissions (environmental quality), except value added hotel and catering services has unidirectional bonds with environmental quality. Furthermore, short-run pairwise causality based tests finalized that a surge in forecasting regressors with forecasted variables, forecasted to forecasting variables, portray a confirmation of feedback hypothesis at a strong significance level, in agreement with [40,45,[68][69][70][71][72][73][74][75][76]. The landscape of retrieved estimates conferred a few guidelines, for BRI, to the Chinese government at the provincial level for initiating renewable based energy projects (solar based, wind based and biomass based projects), which may focus on declining the usage of fossil fuels based energy in industry, transportation, and in the hotel industry.…”
Section: Empirical Results and Discussionmentioning
confidence: 67%
“…Similarly, Shen, et al [ 41 ] see technological innovation as an external driver for achieving high quality development in tourism and urbanization. In a previous study, Chenghu, et al [ 42 ] argued that a large increase in tourists would degrade the environment and be detrimental to the coordination between tourism development, technological innovation, urbanization, and environmental quality; however, this paper holds that the increase in the number of tourists represents the improvement of the development of tourism, providing more employment opportunities for local residents, promoting the local economy, and is conducive to the harmonious development of tourism, urbanization, technology and ecological environment.…”
Section: Discussionmentioning
confidence: 99%